Degradation of cellulose by Aspergillus sp Trichoderma koninggii, and Myriococcum sp. - Masbah, Khatijah; Yaziz, Mohammad Ismail; Chow, Chin Tong (1983)
Culture filtrates obtained from Aspergillus sp, Trichoderma koningii and Myriococcum sp were shown to be active in degrading cotton wool and filter paper. The optimum temperature for growth for Aspergillus sp and T. Koningii occurred at 37° while that of Myriococcum at 45°-50°C. Optimum temperature for activity was recorded as 45° C for T. koningii and 40° C for Aspergillus sp and Myriococcum sp; the pH optima occurred at pH 5.0, 4.0 and 7.0 respectively. The action of these organisms on various cellulosic wastes was tested and pineapple waste was the most amenable to degradation. Synergistical studies using crude enzyme extracts indicated only a small increase in enzyme activity (40%).